DESIGNING A PLAY-BASED HYBRID LEARNING MODEL FOR INDONESIAN KINDERGARTENS; CHALLENGES AND OPPORTUNITIES FOR PARENTAL ENGAGEMENT - Ahmed Shah; Fatima Malik; Mariam Khan (Yayasan Adra Karima Hubbi, 2026)
The integration of play-based learning into hybrid education models for early childhood has become increasingly relevant in post-pandemic Indonesia, where digital adaptation and parental involvement define the quality of kindergarten learning experiences. The research addresses the growing need to design a pedagogically sound and culturally adaptive hybrid learning model that preserves the playfulness essential to early education while leveraging digital tools for continuity and engagement. The study aims to explore the challenges and opportunities of developing a play-based hybrid model that fosters active parental participation and supports children’s socio-emotional and cognitive growth. A qualitative case study design was employed, involving 30 teachers and 50 parents from three kindergartens in West Java. Data were collected through classroom observations, parental interviews, and teacher focus group discussions, analyzed using thematic coding and triangulation to ensure reliability. Findings revealed that while teachers effectively integrated digital play platforms and storytelling sessions, parental engagement varied due to differing levels of digital literacy and home-learning readiness. The study also identified that hybrid play-based activities significantly enhanced children’s motivation and collaborative behavior when parents acted as co-facilitators rather than supervisors. The research concludes that successful hybrid play-based learning in Indonesian kindergartens depends on balanced collaboration between educators, parents, and digital tools. Strengthening parental digital competence and providing structured guidance for home-based play activities can transform hybrid learning into an inclusive, joyful, and developmentally appropriate experience. The study contributes to the broader discourse on hybrid pedagogy in early childhood education and proposes a localized framework for sustainable parental engagement.